TTHE EFFECT OF PROFITABILITY, LEVERAGE, AND FREE CASH FLOW ON DIVIDEND POLICY (EMPIRICAL STUDY ON CONSUMER GOODS COMPANY LISTED ON INDONESIA STOCK EXCHANGE) - Rahmawati, Indah Retno (Jurnal KIAFE, 2023)
This study aims to examine the effect of profitability, leverage, and free cash flow on dividend policy in consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. This type of research is quantitative research. The data used is secondary data in the form of financial reports downloaded from the official website of the Indonesia Stock Exchange (IDX). The research sample was taken using a purposive sampling method and obtained 21 companies that met the criteria. The analysis carried out in this study includes descriptive statistical analysis test, classical assumption test, multiple regression and hypothesis analysis with analysis using SPSS 26 software. The test results simultaneously show that the variables of profitability, leverage, and free cash flow have a significant effect on dividend policy. While the partial test results show that the profitability variable has a positive effect on dividend policy, leverage has a positive effect on dividend policy, while free cash flow has a negative effect on dividend policy.